The Texas Health Presbyterian Hospital of Dallas : recovery strategy after Ebola - Vera, Dusya; Rodriguez, Antonio ([London] : SAGE, 2016)
In October 2014, all the attention of the US media was focused on the Texas Health Presbyterian Hospital of Dallas. This case describes the impact of the first cases of the Ebola virus disease in the United States on the reputation of an iconic hospital in Dallas. The case invites students to provide recommendations of strategic steps that the administration of the hospital can take to resolve the crisis and recover its reputation after this crisis.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Texas Health Presbyterian Hospital of Dallas; Crisis management -- Case studies; Health services administration -- Case studies; Ebola virus disease -- United States -- Case studies